Determinants of Government Spending on Regional Development Inequality in the East Indonesia Area - Fajriani Azis; Andika Isma; Andi Naila Quin Azisah Alisyahbana (Universitas Batanghari Jambi, 2023)
This research aims to analyze the economic conditions specifically in Eastern Indonesia (KTI), which is a maritime-based economic area. The research uses government spending variables with three area, namely education, health and infrastructure on development inequality variables. The research method approach used is panel data regression analysis from 2015 to 2020. The results of this study indicating that there are four variables in this study that influence regional development inequality, these variables are local government spending on education, health and infrastructure, and the human development index. The regional government spending variable in the infrastructure sector has no effect on economic growth variables and the economic growth variable has no effect on development inequality. Analysis of the three variables that have an indirect effect on development inequality, namely local government spending on education and health through the human development index and economic growth, and the human development index variable has an indirect effect on regional development inequality through economic growth. Meanwhile, the variable local government spending on infrastructure does not have an indirect effect on regional development inequality through the human development index and economic growth in Eastern Indonesia.